The reality of the contributions of associations of people with disabilities in achieving their social empowerment: An applied study on care centers for persons with disabilities in the city of Hail - Al-Ashqar, Jawaher Ghazi (Journal of Educational and Psychological Sciences, 2024)
This study aimed to explore the contributions of disability associations in achieving social empowerment for individuals with disabilities in Hail, Saudi Arabia. To achieve the study's objectives, a descriptive-analytical method was employed, using a questionnaire as the primary data collection tool. The study sample consisted of 62 employees working in disability associations in Hail. The results indicated that the contributions of these associations in providing educational services for individuals with disabilities had an average score of 3.99, indicating a high level of effectiveness. The provision of social services received an average score of 4.25, denoting a very high level, while psychological services scored 4.35, also reflecting a very high level of contribution. However, the findings revealed moderate challenges that limit the effectiveness of these associations in delivering empowerment services to individuals with disabilities. Additionally, the study found no statistically significant differences in the responses of participants regarding the contributions of disability associations in achieving social empowerment, attributed to variables such as gender or educational qualification. The study recommended enhancing and improving the quality of social care and empowerment services provided to individuals with disabilities. It also suggested that the Ministry of Human Resources and Social Development and the Ministry of Education increase their focus on addressing the psychological, counseling, and educational needs of students with disabilities who benefit from the services of these associations.
Keywords: People with disabilities; disabilities; social empowerment; associations of people with disabilities